The role of herpesvirus in the paradigm of infectious myocarditis (review) - Peremot, S; Smilyanska, M; Volyanskiy, A; Kashpur, N (Annals of Mechnikov's Institute, 2020)
According to the research of the last decade, there has been growth in the noncoronary disease infarction, increased their share among the causes temporary or persistent disability, disability and deaths. Among others myocarditis, which constitute 11% of all diseases of the cardiovascular system and is responsible for almost 20% of cases of sudden death in people physically safe. The disease is an inflammatory damage to cardiomyocytes, which is caused by direct action or indirectly through immune mechanisms of infectious agents of bacterial, viral, protozoan nature, as well as chemical and physical factors. The term "myocarditis" was first proposed I F Soberheim in 1837 and in 1900. A. Fiedler described the myocardial injury and justified the very concept of primary myocarditis. It is widely accepted that myocarditis - natural complications of infectious diseases in which etiological factor may be any infectious agent. However, at the present stage bacterial pathogens give way to viral. Those viruses according to numerous studies result in the development of myocarditis and consequently lead to the development of myocardial dysfunction. Until recently, most were considered cardiotropic ECHO viruses, Coxsackie group A, B, causing half of all cases of viral myocarditis. However recently reviewed the role of enteroviruses in favor of persistent virus and particularly the family Herpesviridae. The significance in the etiology of myocarditis herpes simplex virus, human herpes type 6, Epstein - Barr virus, cytomegalovirus. Published data indicate that the development of viral myocarditis patients after serous meningoencephalitis caused by the varicella-zoster virus. Widespread herpesvirus diseases their tropism for endothelial cells and myocardium, the capacity for long-term persistence in the body the opportunity to explain virus inducted inflammatory damage to cardiomyocytes. Increased attention to this issue recently linked with the present stage of the study of viral disease characterized by the accumulation of new scientific data obtained through the practice implemented highly informative diagnostic tests: ELISA, immunofluorescence reactions and molecular biological methods. However, despite scientific advances, today viral myocarditis remains less explored disease, myocarditis virus inducted since if they are not diagnosed in the acute phase of viral diseases remain without attention of clinicians in the future are difficult to identify. According to the literature in 24 - 33% of patients, myocarditis course may be clinically latent form and it is not accurate data to determine the absolute frequency of myocarditis. Endomyocardial biopsy (EMB) with immunohistochemical study of biopsy and polymerase chain reaction, which recognized gold standard for diagnosis of myocarditis, requires special equipment and highly qualified experts. In addition, still debate that the EMB diagnostic value and feasibility of its application in specific clinical situations and frequency of complications. When myocarditis may be no correlation changes on ECG, biochemical and clinical data, which significantly complicates diagnosis. Detect viruses in the myocardium can direct method of myocardial biopsy and PCR. This diagnostic importance only positive biopsy results, which in focal myocardial lesions likely to be negative. Animal studies have shown that determine viral replication in the myocardium is possible only in the first two weeks of the disease, when symptoms of myocarditis may not be available or they are minimal. It is shown that determination in serum pro-inflammatory cytokines in myocarditis has a high diagnostic value and could compete with invasive and instrumental methods of diagnosis, however, is not in the arsenal of research laboratories and practical carrying it requires funds. Bring viral myocarditis are also on the rise diagnostically meaningful titer virus neutralizing antibodies in the serum of the patient. However, antibody titer rises slowly, and often the results of this retrospective study have just mentioned. More important is the study of the immunological status of patients. Proof of inflammation in cardiomyocytes an imbalance of T-helper 1 and type 2, which defines the nature of the immune response in myocarditis. Thus, we can say that today there are a number of non-invasive methods of diagnosis of inflammatory lesions cardiomyocytes, which are highly informative. In addition, there is intense accumulation of new scientific data on the etiology and pathogenesis of viral myocarditis. So research aimed at finding clear diagnostic criteria for verification of myocarditis, and more widespread adoption of information and relatively safe methods of diagnosis in clinical practice is especially important and will enhance understanding of the significance of this disease in cardiovascular continuum.